Correlation between tumor necrosis factor-alpha and septic shock in children - Khrisanti Dinata; Ari L. Runtunuwu; Jose M. Mandei; Julius H. Lolombulan (Indonesian Pediatric Society Publishing House, 2013)
Background The crucial role cytokines play in the pathophysiology of sepsis is widely accepted. Infection stimulates the production of cytokines in various cell types. Tumor necrosis factor-alpha (TNF-a) is one of the most extensively investigated cytokines in experimental and clinical sepsis. Tumor necrosis factor-alpha has been shown to mediate lethality in experimental sepsis. Objective To evaluate for a possible correlation between TNF-a level and septic shock in children. Methods This cross-sectional study was conducted in Manado from June to September 2011. A total of 40 patients with a recent diagnosis of sepsis or septic shock were included. Plasma specimens were collected from subjects for measurement of TNF-a concentration. Logistic regression analysis was used to assess the correlation between TNF-a level and sepsis, as well as the probability of shock in children with sepsis, with P<0.05 as statistically significant. Results There was a strong positive correlation between TNF-a level and the probability of shock in children with sepsis (regression coefficient = 0. 78, P = 0.002). Conclusions There is a strong positive correlation between TNF-a level with the probability of shock in children with sepsis. Higher plasma level ofTNF-a is associated with higher probability of septic shock.